Improved Representation for the First Precursor in the Lorentz Medium - Ciarkowski, A. (Engineering Transactions, 2000)
The best methods available nowadays for modelling the propagation of very short (duration less than 100 fs), ultrawideband electromagnetic signals in physical media are the asymptotic ones. Numerical methods loose their traditional leadership due to their inability to handle rapid oscillations of the propagating signal. Therefore it is important to create accurate asymptotic models of propagation which can be used as a reference. In this paper a new description of primary precursor in a dispersive Lorentz medium is given, based on uniform asymptotic theory of evaluation of integrals and a new approximate solution to the distant saddle point equation. The new representation of the signal in the medium is illustrated graphically and compared with the Oughstun-Sherman representation.